2005
DOI: 10.1002/jor.20018
|View full text |Cite
|
Sign up to set email alerts
|

Effect of cyclic strain and plating matrix on cell proliferation and integrin expression by ligament fibroblasts

Abstract: The role of cell surface integrins in cell migration, proliferation, and attachment to matrix molecules is well known. Integrin-matrix interactions have been implicated in mechanotransduction and load transmission from the outside to the inside of the cell. In this study, the effect of cyclic strain on the cell proliferation, attachment, and expression of integrin subunits b1, b3, and a5 was determined in anterior cruciate ligament (ACL) and medial collateral ligament (MCL) fibroblasts grown on polystyrene, Ty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
36
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 53 publications
(37 citation statements)
references
References 35 publications
1
36
0
Order By: Relevance
“…Thus, compared with 2D culture, 3D culture resulted in increased expression of a5b1 in fibroblasts and chondrocytes (Takahashi et al, 2003;Hannafin et al, 2006), b1 subunit in gliomas and breast cancer cells, or a6 in chondrosarcoma (Demou, 2010).…”
Section: Impact Of Mechanical Stress On Integrin Expression and Functionmentioning
confidence: 95%
“…Thus, compared with 2D culture, 3D culture resulted in increased expression of a5b1 in fibroblasts and chondrocytes (Takahashi et al, 2003;Hannafin et al, 2006), b1 subunit in gliomas and breast cancer cells, or a6 in chondrosarcoma (Demou, 2010).…”
Section: Impact Of Mechanical Stress On Integrin Expression and Functionmentioning
confidence: 95%
“…In vertebrate animals, there is substantial and long-established evidence that properly applied mechanical forces are necessary for the appropriate growth, maintenance, and remodeling of musculoskeletal system components. 2,[5][6][7][8][9][10] While there has been a significant research effort focused on mechanobiology of the extracellular matrix, [10][11][12][13][14][15][16][17][18][19][20] there is no consensus on how even the simplest connective tissue structures are initially formed, grown, and maintained. 21,22 Nonetheless, it has been recognized that the mechanical state of a tissue is a potent regulator of (i) fibroblast differentiation state, (ii) migration direction/speed, and (iii) the local secretome.…”
Section: Introductionmentioning
confidence: 99%
“…After 6 and 24 h, increased proliferation was observed following a period of 15 and 60 min of stretching. Furthermore, there have been some reports where an appropriate level of mechanical force was shown to stimulate or inhibit cell proliferation [48][49][50][51][52][53][54][55]. Kaspar et al [56] reported an increase in human osteoblastic cell proliferation and type I collagen propeptide release under mechanical strain (1,000 μ strain, 1 Hz, 30 min/day, for 2 days).…”
Section: Discussionmentioning
confidence: 98%